2000
DOI: 10.1080/09629350050024339
|View full text |Cite
|
Sign up to set email alerts
|

Role of macrophage migration inhibitory factor (MIF) in allergic and endotoxin‐induced airway inflammation in mice

Abstract: Macrophage migration inhibitory factor (MIF) has recently been forwarded as a critical regulator of inflammatory conditions, and it has been hypothesized that MIF may have a role in the pathogenesis of asthma and chronic obstructive pulmonary disease (COPD). Hence, we examined effects of MIF immunoneutralization on the development of allergen-induced eosinophilic inflammation as well as on lipopolysaccharide (LPS)-induced neutrophilic inflammation in lungs of mice. Anti-MIF serum validated with respect to MIF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(15 reference statements)
1
6
3
Order By: Relevance
“…In contrast to what was found in a prior report using neutralizing antibodies [51], our results demonstrated that treatment of mice with anti-MIF in the challenge phase markedly diminished the AHR and the eosinophilic inflammation, but not IgE concentration in the serum or inflammatory mediator concentrations in the BALF. One possibility for this discrepancy is an inefficient neutralization of MIF associated to lower frequency or dose of antibody treatment used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to what was found in a prior report using neutralizing antibodies [51], our results demonstrated that treatment of mice with anti-MIF in the challenge phase markedly diminished the AHR and the eosinophilic inflammation, but not IgE concentration in the serum or inflammatory mediator concentrations in the BALF. One possibility for this discrepancy is an inefficient neutralization of MIF associated to lower frequency or dose of antibody treatment used.…”
Section: Discussioncontrasting
confidence: 99%
“…One could hypothesize that MIF produced by CD4 + cells acts in an autocrine/paracrine fashion regulating the production of IFN-c. On the other hand, the effect of MIF on IL-4 inhibition might involve the action of intracellular MIF. The mechanism by which MIF affects Th cells during the priming phase requires further investigation; however, our results clearly demonstrated that MIF is not required for Th2 polarization.In contrast to what was found in a prior report using neutralizing antibodies [51], our results demonstrated that treatment of mice with anti-MIF in the challenge phase markedly diminished the AHR and the eosinophilic inflammation, but not IgE concentration in the serum or inflammatory mediator concentrations in the BALF. One possibility for this discrepancy is an inefficient neutralization of MIF associated to lower frequency or dose of antibody treatment used.…”
contrasting
confidence: 99%
“…The objective of the experiments described here was to determine the direct effects of two PDE 4 inhibitors, roflumi- LPS challenge, administered as an aerosol or via the intratracheal route, has been shown to induce airway inflammation in mice (Schwartz et al, 1994;Korsgren et al, 2000;Birrell et al, 2004) and rats (Ulich et al, 1995;Haddad et al, 2001). Treatment with roflumilast and piclamilast caused a reduction of neutrophil numbers in the BAL, a finding that agrees with published data.…”
Section: Discussionsupporting
confidence: 75%
“…Cellular inflammation, TNF-␣ levels, and the levels of the neutrophilic chemokines keratinocyte-derived chemokine (KC) and macrophage inhibitory protein (MIP)-2, shown to be established markers of inflammation in response to LPS (Schwartz et al, 1994;Ulich et al, 1995;Korsgren et al, 2000;Haddad et al, 2001;Birrell et al, 2004), were measured in the airway lumen as well as in lung tissue. The effects on these parameters in the circulation were also determined.…”
mentioning
confidence: 99%
“…Only a few reports have examined the potential role of MIF in asthma [12][13][14]. ROSSI et al [12] first reported that MIF levels were increased in BALF from asthmatic patients and that circulating eosinophils could produce MIF upon stimulation in vitro.…”
mentioning
confidence: 99%